A low-cost markerless motion capture system to automate functional gait assessment: Feasibility study - Osman Darici; Chanel Cabak; Jeremy D. Wong (PLoS ONE, 2026)
Functional gait assessments in older adults have traditionally required manual in-person quantification of clinical measures such as walking speed and step placement. This reliance on individuals trained in motion analysis hinders the frequency with which they are performed and reduces their generalizability and replicability. To standardize, simplify, and broaden access to gait assessments we here deploy recently-developed open-source tools to produce a low-cost, AI driven markerless motion capture system with custom analysis software for Functional Gait Assessment. Our system uses 3 Cameras and was validated with a traditional marker-based system on subjects (N = 3), showing strong correlation to laboratory-standard measures of step length ( R 2 = 0.98), step width ( R 2 = 0.97), and head speed ( R 2 = 0.95). The markerless system’s FGA reports demonstrated data similar to previous FGA findings in older adult subjects (N = 5). Moreover, supplemental standard biomechanical gait measures Step Width, walking Duration, and continuous Gait Speed may be integrated to augment existing FGA. This study demonstrates a proof-of-principle open-source markerless system for analyses of functional gait.